Prophetic Education as a Preventive Approach to Radicalization among Veiled Female Students - Luthfiyah; Ruslan; Nazilla, Sazkia; Wahyono, Zubaidi (Cendekia: Kependidikan dan Kemasyarakatan, 2025)
The veiled student is still debatable and faces negative stigma from society, such as Islamic fundamentalist groups, radicalists, terrorists, exclusive groups, and adherents of deviating ideologies. This research aims to find out the veiled student responses to that negative stigma and give prophetic education by transforming prophetic values so that they understand and implement them in their life as individuals and social humans. This qualitative research used a purposive sampling technique. Data collection techniques were in-depth interviews, observation, and focus group discussion. Data analysis used NVivo 14 software, which serves as an analytical tool that clarifies and strengthens the interpretation of qualitative data by visualization of data coding results. The results show that the veiled student has been aware of negative stigma from society. Their responses are positive and negative, with internal and external strategies. The prophetic education and veiled law by focus group discussion indicated that the informant shows an open attitude, accepts the understanding of prophetic values, and all of the subject matter about veiled law in Islam and radicalism. That understanding of prophetic education can be based on their implementation in their life as individuals and social humans, until the efforts to prevent Islamic radicalism based on Islamic institutions can be achieved.